Analisis Biaya Dan Pendapatan Usahatani Jagung Pada Pemanfaatan Lahan Tidur Di Kelurahana Malalayang Satu Timur Kecamatan Malalayang Kota Manado - Saragih, Monica; Lolowang, Tommy Fredy; Laoh, Esry Olly Harryani (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
The purpose of this research is to analyze the cost of corn farming income on idle land utilization in Malalayang Satu Timur Village, Malalayang Subdistrict. the data used is using primary and secondary data, primary data obtained from survey interviews and observations. secondary data ob-tained from information or data related to the analysis of corn farming income on idle land utiliza-tion and other sources in the form of documents from Malalayang Satu Timur Village and Manado City National Land Agency. The analysis method used in this research is quantitative descriptive analysis analysis. The results of the study based on the analysis on the utilization of idle land in corn farming with a total revenue of IDR 105,000,000. while the total cost of corn farming amounted to IDR 75.500.000. Then the income obtained for one planting season is IDR 29.500.000 from the area of utilization of idle land cultivating corn with a land area utilized 3.5 ha.